Pengaruh Pemberian Kompos Pada Pertumbuhan dan Produktivitas Tanaman Bawang Merah (Allium cepa L.) - Riki Ruhimat; Gunawan Djajakirana; Sarjiya Antonius (Institut Pertanian Bogor, 2023)
Shallot productivity relies on diverse environmental conditions, including soil fertility. Compost is an organic material that is crucial for the improvement of soil health and fertility. Compost amendment could be employed on shallot to improve its growth and productivity. This study aims to investigate the effect of 4 different composts amendments, processed with 4 different bioactivators, on the shallot growth (Bima–Brebes variety), the dynamic of culturable microbes, and nutrient content on the growth medium inside the polybag. Treatments include a mature compost processed with no biactivators (K0), and with the bioactivator Bioaktimo (K1), Beyonic Startmik (K2), indigenous (K3), and the mixed of K1, K2, and K3 (K4). Measured parameters on shallot growth include plant height, number of leaves, stem diameter, wet and dry weights of shallot bulb, root, and above-ground biomass, and chlorophyll content. In addition, physical, chemical, and biological characteristics of the initial planting medium on the polybag were determined. The result showed that compost amendment significantly increased all parameters tested, except chlorophyll content, when compared to the control and the treatment with 100% chemical fertilizer. The best shallot growth was found in the treatment with soil planting media of 75% Soil + 25% Compost K4 (TK5). Keywords: organic fertilizer, bioactivator, shallot